Systems modelling as an approach for understanding and building consensus on non-communicable diseases (NCD) management in Cambodia - John P. Ansah; Amina Mahmood Islam; Victoria Koh; Vanthy Ly; Hero Kol; David B. Matchar; Chhun Loun; Mondol Loun (BMC, 2019)
Abstract Background This paper aims to demonstrate how systems modeling methodology of Group Model Building (GMD) can be applied for exploring and reaching consensus on non-communicable disease (NCD) management. This exercise was undertaken as a first step for developing a quantitative simulation model for generating credible estimates to make an investment case for the prevention and management of NCDs. Methods Stakeholder engagement was facilitated through the use of a Group Model Building (GMB) approach. This approach combines various techniques in order to gain a whole system perspective. Results A conceptual qualitative model framework that connects prevention-via risk factors reduction-screening and treatment of non-communicable diseases (NCDs) was developed with stakeholders that draws on stakeholders personal experiences, beliefs, and perceptions through a moderated interactions to gain in-depth understanding of NCDs management. Conclusion Managing NCDs in Cambodia will require concerted effort to tackle NCD risk factors, identifying individuals with NCDs through screening and providing adequate and affordable consistent care to improve health and outcomes of NCDs.